Effect of Routine Consumption of Turmeric-Tamarind Herb on Dysmenorrhea among Adolescent Girls - Safitri Safitri; Gustina Gustina (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2023)
Puberty in adolescents is identified by the sign of monthly menstrual period. Although it occurs naturally, many adolescent girls suffer from dysmenorrhea. Dysmenorrhea affects daily activities and even causes absence from school. Herbal medicine is still an alternative therapy for dysmenorrhea among adolescent girls. Non-pharmacological therapy using turmeric-tamarind herb is easy to obtain and has no side effects. This study aims to determine the effect of routine consumption of turmeric-tamarind herb on dysmenorrhea among adolescent girls in Pondok Meja Village. This was an observational analytical study with cross-sectional design. The population in this study involved all adolescent girls in Pondok Meja Village, with a total sample of 76 adolescent girls, who were selected using a purposive sampling technique based on inclusion and exclusion criteria. Data was collected using online questionnaires from December 2021 to April 2022. Data collected were analyzed using Chi-Square test. Results showed that there was an effect of routine consumption of turmeric-tamarind herb on dysmenorrhea among adolescent girls. Adolescent girls who did not routinely consume turmeric-tamarind herb had a 0.035 times higher probability of experiencing primary dysmenorrhea than those who routinely consume turmeric-tamarind herb. Adolescent girls who routinely consumed turmeric-tamarind herb did not experience dysmenorrhea.